ANALISIS BENTUK PILAR JEMBATAN TERHADAP POTENSI GERUSAN LOKAL (Studi kasus Model Pilar Penampang Persegi Panjang dan Ellips) - Anton Ariyanto (Universitas Pasir Pengaraian, 2010)
Pilar is a structure under the bridge. The presence of pillars in river flow cause changes in river flow patterns. These changes include the formation of down flow (downward flow) and Horseshoe vortex (horseshoe vortex) around the pillar. Changes in flow pattern will result in local scour around the pillar. Local scour is going on around the pillar causes the river bottom around the pillar so that the water flow transported formed scour hole. Scour hole is formed can destabilize the pillar. Stability is very important pillar in the forwarding function of vehicle load to the foundation. This study aims to determine the maximum scour depth value of each form the pillars for any changes debit.Penelitian is done on a permanent uniform flow conditions (steady uniform flow) with three variations of flow rates that occur within the capacity of the appliance Multy-purpose teaching flume.